2018
DOI: 10.1371/journal.pone.0193380
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical pharmacology of AZD9977: A novel mineralocorticoid receptor modulator separating organ protection from effects on electrolyte excretion

Abstract: Excess mineralocorticoid receptor (MR) activation promotes target organ dysfunction, vascular injury and fibrosis. MR antagonists like eplerenone are used for treating heart failure, but their use is limited due to the compound class-inherent hyperkalemia risk. Here we present evidence that AZD9977, a first-in-class MR modulator shows cardio-renal protection despite a mechanism-based reduced liability to cause hyperkalemia. AZD9977 in vitro potency and binding mode to MR were characterized using reporter gene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 70 publications
8
78
0
1
Order By: Relevance
“…Administration of AZD9977 and the associated increases in serum aldosterone levels were not, however, accompanied by any alteration in urinary electrolyte excretion or serum levels of potassium or other electrolytes ( Figure b , Figure ). These results are consistent with a differentiated mechanism of action of AZD9977 when compared with other MR antagonists and are in agreement with the findings in rats fed a low‐salt diet, in which AZD9977 also had no effect on the urinary sodium to potassium ratio . The observations made in this study suggest AZD9977 has a unique mode of action supporting early reported findings of MR modulation rather than antagonism.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Administration of AZD9977 and the associated increases in serum aldosterone levels were not, however, accompanied by any alteration in urinary electrolyte excretion or serum levels of potassium or other electrolytes ( Figure b , Figure ). These results are consistent with a differentiated mechanism of action of AZD9977 when compared with other MR antagonists and are in agreement with the findings in rats fed a low‐salt diet, in which AZD9977 also had no effect on the urinary sodium to potassium ratio . The observations made in this study suggest AZD9977 has a unique mode of action supporting early reported findings of MR modulation rather than antagonism.…”
Section: Discussionsupporting
confidence: 92%
“…20,21 AZD9977 is a nonsteroidal, selective MR modulator that blocks the damaging action of aldosterone and cortisol in nonepithelial tissues, but has minimal effects on electrolyte handling by kidney epithelial cells. 25 This tissue-specific modulation means AZD9977 could provide protection against the progression of cardiovascular and renal disease in patients with HFpEF, CKD, or both diseases, without the risk of hyperkalemia associated with steroidal MR antagonists, such as spironolactone and eplerenone. The binding of AZD9977 to the MR induces a unique protein conformation in the MR that is distinct from the one induced by MR antagonists, and may modify the interaction pattern of the receptor with transcriptional co-activators.…”
Section: Initial Clinical Experience With Azd9977mentioning
confidence: 99%
See 2 more Smart Citations
“…67 The effect of endothelial EnNaC deletion in promoting better recovery from hypoxia may be related to the increased generation of NO, thus preventing sustained vasoconstriction and allowing better kidney perfusion. [77][78][79] In a similar model, which uses DOCA administration instead of aldosterone, specific MR deletion in the endothelium ameliorated cardiac remodelling, but not renal injury, suggesting that the MR in the endothelium is not directly involved in this type of kidney injury and that other cell types in which the MR is expressed, such as inflammatory smooth muscle cells, must be involved. 67 Kidney fibrosis has been widely studied in the 5/6 nephrectomy model, in which aldosterone has shown to play a key role.…”
Section: Mrs In Kidney Injurymentioning
confidence: 99%